Enhanced diagnostics of radiating relativistic singularities and BISER by nonlinear post-compression of optical probe pulse. (1st July 2022) - Kotov, A.V.; Esirkepov, T.Zh.; Soloviev, A.A.; Sagisaka, A.; Ogura, K.; Bierwage, A.; Kando, M.; Kiriyama, H.; Starodubtsev, M.V.; Khazanov, E.A.; Mironov, S.Yu.; Pirozhkov, A.S.
Abstract: The enhancement of the resolution of pump-probe optical diagnostics for ultrafast processes by compressing the probe pulse duration using the CafCA approach [1] is considered on an example of the BISER soft-X-ray generation [2] with the J-KAREN-P laser [3].